Selective Targeting of Serotonin 5-HT1a and 5-HT3 Receptors Attenuates Acute and Long-Term Hypersensitivity Associated With Neonatal Procedural Pain - de Kort, Anne R.; Joosten, Elbert A.; Patijn, Jacob; Tibboel, Dick; van den Hoogen, Nynke J. (Frontiers in Pain Research, 2022)
Neonatal painful procedures causes acute pain and trigger long-term changes in nociceptive processing and anxiety behavior, highlighting the need for adequate analgesia during this critical time. Spinal serotonergic receptors 5-HT1a and 5-HT3 play an important role in modulating incoming nociceptive signals in neonates. The current study aims to attenuate acute and long-term hypersensitivity associated with neonatal procedural pain using ondansetron (a 5-HT3 antagonist) and buspirone (a 5-HT1a agonist) in a well-established rat model of repetitive needle pricking. Sprague-Dawley rat pups of both sexes received ondansetron (3 mg/kg), buspirone (3 mg/kg) or saline prior to repetitive needle pricks into the left hind-paw from postnatal day 0–7. Control animals received tactile stimulation or were left undisturbed. Acute, long-term, and post-operative mechanical sensitivity as well as adult anxiety were assessed. Neonatal 5-HT1a receptor agonism completely reverses acute hypersensitivity from P0-7. The increased duration of postoperative hypersensitivity after re-injury in adulthood is abolished by 5-HT3 receptor antagonism during neonatal repetitive needle pricking, without affecting baseline sensitivity. Moreover, 5-HT1a and 5-HT3 receptor modulation decreases adult state anxiety. Altogether, our data suggests that targeted pharmacological treatment based on the modulation of spinal serotonergic network via the 5-HT1a and 5-HT3 receptors in neonates may be of use in treatment of neonatal procedural pain and its long-term consequences. This may result in a new mechanism-based therapeutic venue in treatment of procedural pain in human neonates.